2022
DOI: 10.25259/csdm_100_2022
|View full text |Cite
|
Sign up to set email alerts
|

Impact of mask wear on the skin of clinical year medical students during the COVID-19 pandemic: A cross-sectional study

Abstract: Objectives: Use of facial masks since the onset of the COVID-19 pandemic has led to a new type of mechanical acne termed Maskne. Long-term wear of masks can increase skin damage leading to de novo onset of, or worsening of pre-existing facial dermatoses such as acne, rosacea, and dermatitis. We have encountered numerous studies on the effects of mask wear on skin of health-care professionals, mainly COVID-19 first responders, but there seems to be scarce literature on the effects of mask wear in medical studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…usage, it becomes a civic responsibility to wear face masks both for personal protection and for others during the COVID-19 pandemic. 7 The majority of the participants in this study used the recommended triple-layered surgical mask, which was similar to the findings of the Polish study, 6 where 42.4% and in a study done in Georgia, 8 where 80.8% medical students used the same. In the study done in Raipur, India, N95 was used by 74.5% of medical students.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…usage, it becomes a civic responsibility to wear face masks both for personal protection and for others during the COVID-19 pandemic. 7 The majority of the participants in this study used the recommended triple-layered surgical mask, which was similar to the findings of the Polish study, 6 where 42.4% and in a study done in Georgia, 8 where 80.8% medical students used the same. In the study done in Raipur, India, N95 was used by 74.5% of medical students.…”
Section: Resultssupporting
confidence: 82%
“…As many as 61.4% of face mask users in this study did not replace the disposable type of face mask every day, as also reported by 58.9% of participants in a study done in Georgia. 8 As per the recommendations, disposable face masks need to be replaced every day. 12 In the present study, disposable face masks, when moist, were not discarded on every occasion by 48.1% of the 295 face mask users.…”
Section: Resultsmentioning
confidence: 99%